Functional diversity dynamics of waterbird communities driven by water levels at Shengjin Lake, a small river‐connected shallow lake in the middle and lower Yangtze River floodplain - Yongzhi Wang; Xianglin Ji; Lizhi Zhou (Ecology and Evolution, 2024)
Abstract Gate‐controlled activities in lakes can directly or indirectly influence the assembly of waterbird communities. Shengjin Lake, a Ramsar site, is a typical river‐connected and gate‐controlled shallow lake in the lower and middle Yangtze River floodplain in China, comprising three sub‐lakes (upper, middle, and lower) based on topographical features. We surveyed wintering waterbirds at Shengjin Lake from October 2022 to March 2023. We divided the winter water level period into nine phases based on the characteristics of water level changes. By measuring functional diversity, we aimed to provide insights into the differences in waterbird communities among the three sub‐lakes under different water level conditions. Multiple linear regression was used to analyze the relationship between habitat factors and functional diversity. We further explored the relationship between specific functional traits and habitat factors through a combination of the R‐mode linked to the Q‐mode and the trait‐environment correlation matrix (fourth‐corner analyses) to explain the mechanism underlying waterbird community assembly. When the water level fluctuated in the range of 10.43–10.74 m (Huanghai elevation), the three sub‐lakes had significant habitat differences and high habitat heterogeneity, increasing functional richness and functional dispersion of the upper and lower lakes, both of which significantly differed from those of the middle lake. Habitat heterogeneity and mudflat habitats have positive effects on functional diversity. The difference in functional diversity was primarily determined based on the foraging traits and strata of waterbirds. Habitat filtering of particular traits is a major driving force underlying the assembly of waterbird communities. Overall, we suggest that the minimum water level in the wintering period at Shengjin Lake should be regulated between 10.43 and 10.74 m. These findings provide reasonable suggestions for water level regulation and a theoretical basis for conserving waterbird diversity at Shengjin Lake.